2009
DOI: 10.1242/jcs.041137
|View full text |Cite
|
Sign up to set email alerts
|

The yeast endocytic protein Epsin 2 functions in a cell-division signaling pathway

Abstract: The epsins are a family of adaptors involved in recruiting other endocytic proteins, binding of ubiquitylated cargo and induction of membrane curvature. These molecules bear a characteristic epsin N-terminal homology (ENTH) domain and multiple peptide motifs that mediate protein-protein interactions. We have previously demonstrated that the ENTH domain of epsin is involved in Cdc42 signaling regulation. Here, we present evidence that yeast epsin 2 (Ent2) plays a signaling role during cell division. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
5
24
0
2
Order By: Relevance
“…We also showed that cell division defects caused by overexpression of a hyperactive Bem3 mutant (Bem3 D1-114 ) were suppressed by co-overexpression of the endocytic protein, Ent2 (Mukherjee et al, 2009). Further supporting the role of vesicle trafficking in Bem3 localization, Bem3 has been reported to localize to an unidentified intracellular compartment (Knaus et al, 2007) and actin cables have been shown to play an essential role in its transport to polar sites (Knaus et al, 2007).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…We also showed that cell division defects caused by overexpression of a hyperactive Bem3 mutant (Bem3 D1-114 ) were suppressed by co-overexpression of the endocytic protein, Ent2 (Mukherjee et al, 2009). Further supporting the role of vesicle trafficking in Bem3 localization, Bem3 has been reported to localize to an unidentified intracellular compartment (Knaus et al, 2007) and actin cables have been shown to play an essential role in its transport to polar sites (Knaus et al, 2007).…”
Section: Introductionsupporting
confidence: 52%
“…We have previously reported that cell division defects resulting from overexpression of the constitutively active Bem3 mutant (Bem3 D1-114 ) in yeast (Kadota et al, 2004) are rescued by cooverexpression of the endocytic protein Ent2 (Mukherjee et al, 2009). Therefore, we hypothesized that vesicle trafficking, including endocytosis, plays an important role in the regulation of Bem3 activity.…”
Section: Bem3 Binds Phosphoinositides Through Its Ph Domain and This mentioning
confidence: 98%
“…But we note that GFP-Ent1 and GFPEnt2 were previously shown to complement an ent1D ent2D mutant, so it seems unlikely that their differences are caused solely by the tag (Watson et al, 2001). Moreover, other studies have shown that the two endocytic epsins have functions that are not completely overlapping (Baggett et al, 2003;MaldonadoBáez et al, 2008;Mukherjee et al, 2009;Newpher et al, 2005;Wendland et al, 1999). Further studies will be needed to explain the differences in adaptor behavior during endocytosis.…”
Section: Resultsmentioning
confidence: 76%
“…79 This observation, along with the involvement of the RE and the exocyst, further expand the similarities with the cases of Bem3/Ocrl1. Indeed, Bem3 42 and Ocrl1 (Aguilar lab, unpublished results) are epsin-interacting partners as well. Collectively, these studies indicate conservation of the functions of the small GTPase binding proteins in polarized membrane traffic.…”
Section: The Role Of Small Gtpases and Recycling Endosomes In Neuronamentioning
confidence: 94%
“…41 Not surprisingly, Bem3 colocalizes with septins both at the polar cap prior to bud emergence, and at the bud neck during cytokinesis. 40,42 A recent study from our lab established that Bem3 also localizes to an intracellular compartment that is distinctly visible during early stages of the cell cycle. 37 Indeed, electron micrographs revealed that Bem3 occupies a cluster of vesicles polarized toward the emerging bud ( Fig.…”
Section: Small Gtpase Binding Proteins and Their Role In Spatiotempormentioning
confidence: 98%